Report on the Measurement of International Capital Flows : Background Papers. (International Monetary Fund, 1992)
The Background Papers gathers together a number of studies that were prepared as research to the final report. Although not a part of the report itself, these papers provide detail on a number of issues grouped together here by general topic; data sources and methodology, direct investment, portfolio investment, international banking statistics, and other capital flows.